2006
DOI: 10.1007/bf02850219
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of insulin resistance in nondiabetic nonobese patients with chronic kidney disease

Abstract: This study was undertaken to evaluate the prevalence of insulin resistance (IR) and associated factors in nondiabetic, nonobese patients with chronic kidney disease (CKD) who had not yet received dialysis therapy. A group of 89 consecutive patients (42 male, 47 female) who were hospitalized in the Nephrology Clinic at Dicle University, had recently been diagnosed with CKD, and had not yet been treated with dialysis were enrolled in the study, as was a control group of 30 healthy volunteers. Diabetic and obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…38 The third one is insulin, of which circulating plasma levels have been found frequently elevated in patients with a reduced glomerular filtration rate. 39,40 The final one is a decreased brain NO availability reported in renal failure and potentially responsible for the renal disease-related sympathetic activation. 41 Our study has some limitations but also a clinical implication.…”
Section: Discussionmentioning
confidence: 99%
“…38 The third one is insulin, of which circulating plasma levels have been found frequently elevated in patients with a reduced glomerular filtration rate. 39,40 The final one is a decreased brain NO availability reported in renal failure and potentially responsible for the renal disease-related sympathetic activation. 41 Our study has some limitations but also a clinical implication.…”
Section: Discussionmentioning
confidence: 99%
“…Sit et al [4] estimated IR at 48.3% in CKD patients. Unfortunately, there is no normal cut-off level for the HOMA-IR, the standard method for quantification of IR.…”
Section: Discussionmentioning
confidence: 99%
“…Further clinical studies in humans support the link between β-cell dysfunction and CKD [3]. On the other hand, several researchers have cited IR as a primary reason behind hyperglycemia in patients with CKD [4]. It is suggested that IR occurs early with minimal decrease in glomerular filtration rate (GFR) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Sit et al [16] evaluated the prevalence of IR in 89 nondiabetic nonobese patients with chronic kidney disease. At HOMA-IR cutoff 5.4, they reported IR in 48.3% of their chronic kidney disease patients [16] .…”
Section: Impaired Insulin Action In Uremiamentioning
confidence: 99%
“…At HOMA-IR cutoff 5.4, they reported IR in 48.3% of their chronic kidney disease patients [16] . In another study [17] , it was reported in 50% of such patients.…”
Section: Impaired Insulin Action In Uremiamentioning
confidence: 99%